Legalism without adversarialism?: Bureaucratic legalism and the politics of regulatory implementation in the European Union - Chase Foster (Regulation & Governance, 2023)
Many scholars predict that European integration will foster adversarial legalism in Europe. In this article, I empirically assess the Eurolegalism thesis by examining EU regulatory mandates in the competition and securities fields, two policy areas where adversarial legalism is seen as most likely to develop. I argue that the diffusion of adversarial legalism to Europe has faced significant political opposition in the EU policymaking process which has curtailed the use of private enforcement mandates in EU secondary legislation. European policymakers have relied more on administrative enforcement through public regulatory agencies, a mode of policy implementation closer to bureaucratic legalism. In practice, public authorities play the primary enforcement role and private litigation serves the narrower function of compensation following public enforcement actions. Drawing from institutionalist theory, I identify several factors that have encouraged the development of bureaucratic rather than adversarial styles of European legalism, especially member states' commitments to procedural subsidiarity, the negative feedback effects from the US experience with entrepreneurial litigation, and the stickiness of European legal and bureaucratic traditions.
Keywords: 330; adversarial legalism; bureaucratic legalism; competition; European Union; securities